2018
DOI: 10.17116/oftalma201813404141
|View full text |Cite
|
Sign up to set email alerts
|

Endothelins and dopamine levels in tears for assessment of neurovascular disorders in glaucoma

Abstract: Multidirectional changes of endothelins and DA levels in tears of patients with POAG was found. The increased concentration of ET-1 and its precursor bET promote vasoconstriction and decrease of aqueous humor outflow. The decrease of DA concentration is typical for neurodegenerative processes. Estimation of DA and endothelins concentrations in tears can enable early detection of neurovascular disorders in glaucoma patients and help evaluate their severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…3,[8][9][10][11] In a study analyzing the ET-1 levels in tears in patients with glaucoma, the mean ET-1, level was 2.74±0.99 pg/mL in healthy controls, which is similar to our findings. 26 In a rabbit study, the concentration of ET-like immunoreactivity was found to be 13.85±3.94 pg/mL and 15-fold higher than that in plasma. 27 Endothelium may secrete ET-1 in various tissues.…”
Section: Discussionmentioning
confidence: 91%
“…3,[8][9][10][11] In a study analyzing the ET-1 levels in tears in patients with glaucoma, the mean ET-1, level was 2.74±0.99 pg/mL in healthy controls, which is similar to our findings. 26 In a rabbit study, the concentration of ET-like immunoreactivity was found to be 13.85±3.94 pg/mL and 15-fold higher than that in plasma. 27 Endothelium may secrete ET-1 in various tissues.…”
Section: Discussionmentioning
confidence: 91%
“…The risk of developing glaucoma by patients with PD increases by 30% [ 79 ]. The concentration of catecholamines, including dopamine, in aqueous humor and lacrimal fluid was found to be decreased in patients with glaucoma compared to healthy people, attesting to the fact that glaucoma causes a dysfunctioning of the dopaminergic system of the eye [ 79 , 104 ]. The etiology of glaucoma, as well as that of PD, is multifactorial.…”
Section: Eye Disorders During Pd (Glaucoma and Cataract): Clinicalmentioning
confidence: 99%
“… 6 Numerous studies have confirmed the presence of symptoms of visual dysfunction in patients with PD. 7 9 Moreover, visual dysfunction has been reported as a potential biomarker with high specificity in the early stage of neurodegenerative diseases. 10 , 11 In recent years, retinal degeneration in patients with PD has received widespread research attention and has become one of the research hotspots in the field of neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%